PENGARUH KOMITMEN MANAJEMEN PADA KUALITAS PELAYANAN TERHADAP KEPUASAN KERJA KARYAWAN DAN KINERJA PELAYANAN DENGAN EFEKTIVITAS KETERLIBATAN KARYAWAN SEBAGAI PEMEDIASI - BAMBANG SATRIO NUGROHO (Riset Manajemen dan Akuntansi, 2016)
Employees will build a positive attitude and commitment to the organization when the organization demonstrates its commitment to employees. Employees are involved in organizational decision-making will be satisfied and can improve its performance . The purpose of this study was to analyze the effect of management commitment to service on employee job satisfaction and service performance to the effectiveness of employee engagement as a mediating variable. The population in this study were employees and students STMIK Sinar Nusantara Surakarta. Sampling technique in this study using a random sampling and number of samples used by 80 respondents . Methods of data collection using a questionnaire, while the method of data analysis using Path Analysis. Results of this study indicate that management commitment to service has significant positive effect on employee job satisfaction, service performance and effectiveness of employee involvement. Effectiveness of employee involvement had no significant effect on job satisfaction and service performance. Mediation analysis results showed that the effectiveness of employee engagement are not mediated effect of management commitment to service on employee job satisfaction and service performance . Keywords: management commitment, Effectiveness of employee involvement, job satisfaction, service performance